2018
DOI: 10.1002/cyto.b.21754
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of plasma cell myeloma minimal residual disease testing by flow cytometry in an international inter‐laboratory study: Is it ready for primetime use?

Abstract: Background Minimal/measurable residual disease (MRD) testing by flow cytometry (FC) has been proposed as a potential surrogate clinical endpoint in plasma cell myeloma (PCM) clinical trials. As a result, effort has gone into standardizing this approach on PCM patients. Aims To assess inter‐laboratory variation in FC MRD testing of PCM patients in an independent inter‐laboratory study. Methods A dilution series of five stabilized bone marrow samples manufactured to contain 0%, 0.1%, 0.01%, 0.001%, and 0.0001% n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 29 publications
0
25
0
Order By: Relevance
“…This is clearly highlighted in this issue in the work presented by Scott et al , who report on the high sensitivity and good linearity observed in an International Inter‐Laboratory Study based on dilutional series of MM samples. Overall, high (but variable) sensitivity was observed among the participating centers, with good linearity, associated with greater levels of variability for low vs higher PC numbers . Of note, despite the fact that the participating laboratories were all experienced laboratories, deviations from consensus recommendations in panel design, fluorochrome conjugates, lysing reagents occurred, in parallel to specific analytical and post‐analytical errors.…”
Section: Multiple Myelomamentioning
confidence: 81%
See 3 more Smart Citations
“…This is clearly highlighted in this issue in the work presented by Scott et al , who report on the high sensitivity and good linearity observed in an International Inter‐Laboratory Study based on dilutional series of MM samples. Overall, high (but variable) sensitivity was observed among the participating centers, with good linearity, associated with greater levels of variability for low vs higher PC numbers . Of note, despite the fact that the participating laboratories were all experienced laboratories, deviations from consensus recommendations in panel design, fluorochrome conjugates, lysing reagents occurred, in parallel to specific analytical and post‐analytical errors.…”
Section: Multiple Myelomamentioning
confidence: 81%
“…Overall, high (but variable) sensitivity was observed among the participating centers, with good linearity, associated with greater levels of variability for low vs higher PC numbers (21). Of note, despite the fact that the participating laboratories were all experienced laboratories, deviations from consensus recommendations (22)(23)(24) in panel design, fluorochrome conjugates, lysing reagents occurred, in parallel to specific analytical and post-analytical errors.…”
Section: Multiple Myelomamentioning
confidence: 93%
See 2 more Smart Citations
“…To achieve the sensitivities of 10 ‐5 ‐ 10 ‐6 required for MRD assessment, more cells than can normally be obtained from 100 μL of blood or bone marrow are required (4). Laboratories have developed several methods to obtain the 5‐10 x 10 6 cells per tube required for MRD assays but a standardized approach is needed (5). One method, the bulk lyse approach, described by the EuroFlow Consortium has become the de facto standard (6), but in comparison to routine methods it is labor intensive.…”
mentioning
confidence: 99%